Monarchy of Concordia: Business Models and Noise Behavior Legislation - Dehra, Himanshu (Monarchy of Concordia: Business Models and Noise Behavior Legislation, 2021)
Monarchy of Concordia is a globalized society with objective of maintaining peace and harmony in the world by controlling human noise behavior. The Monarchy of Concordia has motto of “Controlling Human Noise Behavior” with guiding principles of energy perspectives in a society. Noise is defined as a sensation of unwanted intensity of a wave. It is perception of a pollutant and a type of environmental stressor. The unwanted intensity of a wave is a propagation of noise due to transmission of energy source waves (viz. physical agents) such as sun, light, sound, heat, electricity, fluid and fire. Human Noise Behavior is checked by identifying a source and a sink of noise i.e. a person making noise and a person affected by such noise. Full globalization requires the harmonization of trade regulations and laws across countries. Such harmonization would require a global government. To overcome all such barriers and national sovereignty issues, a globalized society for maintaining peace and harmony among nations through monitoring and controlling human noise behavior of the world came into existence by establishing sovereign political power of monarchy of Concordia. This monograph is focusing on socio-economic and ergonomics aspects of monitoring and controlling human noise behavior by establishing sovereign political power of Monarchy of Concordia. This monograph is elaborating sustainable development business models of socio-economic aspects for monitoring and controlling human noise behavior in the sovereign political power of Monarchy of Concordia. Legislation aspects of controlling human noise behavior and climate change in monarchy of Concordia are briefly outlined in this monograph. Taxes and fines on noise behavior along with the discussions on various aspects of controlling human noise behavior are also elaborated in this monograph.